Expanding youth employment in the Arab Region and Africa - Joachim von Braun; Chiara Kofol (University of Bonn, Center for Development Research (ZEF), 2017)
The low level and adverse trends of youth employment in Africa and in the Middle East in the last decade are key driving factors of poverty, stress migration, frustration and political instability. There needs to be a sense of urgency to change the situation. How can employment, especially for youth, be created rapidly in these regions? The paper discusses different policies for the generation of mass employment of both skilled and unskilled labor. The sectoral priorities differ within the regions, with rural and agricultural jobs playing a more significant role in Sub-Saharan Africa (SSA). Both SSA and the Arab region show potentials for largescale public works programs. Un-orthodox economic policy actions are called for due to the pressing nature of the youth unemployment situation. These policies should aim at generating productive employment improving skills, and can be implemented both at the central and at the local level. Countries should be responsible for ownership, accountability and self-monitoring of policies and programs. Large scale international funding support should be considered when planning, implementation and supervision are actually credible and results oriented.
Keywords: 330; youth employment; human capital; labor policies